2016
DOI: 10.1007/978-3-319-25474-6_35
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Neural Indices of Continuous Speech Processing at the Phonetic Level

Abstract: The human ability to understand speech across an enormous range of listening conditions is underpinned by a hierarchical auditory processing system whose successive stages process increasingly complex attributes of the acoustic input. In order to produce a categorical perception of words and phonemes, it has been suggested that, while earlier areas of the auditory system undoubtedly respond to acoustic differences in speech tokens, later areas must exhibit consistent neural responses to those tokens. Neural in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This was calculated as the sum of the three band-limited envelopes that compose the S representation. In previous work, our framework has also included a phonemic representation of the speech (a multivariate time series of forced aligned phonemes, similar to F; Di Liberto and Lalor, 2016 ). However, because of the limited amount of speech data used in the present study, less frequent phonemes would not have a sufficient number of occurrences to produce a good model fit.…”
Section: Methodsmentioning
confidence: 99%
“…This was calculated as the sum of the three band-limited envelopes that compose the S representation. In previous work, our framework has also included a phonemic representation of the speech (a multivariate time series of forced aligned phonemes, similar to F; Di Liberto and Lalor, 2016 ). However, because of the limited amount of speech data used in the present study, less frequent phonemes would not have a sufficient number of occurrences to produce a good model fit.…”
Section: Methodsmentioning
confidence: 99%
“…In defining TRFs, it is also possible to include additional covariates, such as linguistic information. Di Liberto and colleagues (DiLiberto, O'Sullivan, & Lalor, 2015;Liberto & Lalor, 2016) took a modelbased approach to entrainment and found that the inclusion of phonemic labels in addition to the speech envelope improve the model's ability to predict EEG data in all frequency bands. Note phonemes are not present at any instant in the acoustic signal, so phonemic labels encode temporally diffuse aspects of the latent linguistic signal.…”
Section: Statistical Models Of the Temporal Responsementioning
confidence: 99%
“…However, while these results are promising, the correlation between the behavioral and objective measures of speech intelligibility only explained 50% of the variance, and the objective measure could only be derived in three-quarter of the subjects. Recently, Di Liberto et al (2015Liberto et al ( , 2016Liberto et al ( & 2017 showed that the cortical tracking of running speech is better characterized using a model integrating both low-level spectro-temporal speech information (e.g., the speech envelope) and discrete higher-level phonetic features.…”
Section: Introductionmentioning
confidence: 99%